Síntese e desempenho de catalisadores com estrutura do tipo pirocloro para produção de gás de síntese - Ramon, Adriana Paula (Universidade Federal de São Carlos, 2016)
Dry reforming of methane (DRM) is a promising process in syngas generation with low molar H2/CO ratio. Syngas production is of great interest for many processes, such as obtaining liquid fuels by Fischer-Tropsch. The main problem in DRM is the large formation of carbon depositions over the catalyst. Catalyst with pyrochlore structure, A2B2O7, presents uniform distribution of active metals into the lattice, resulting in a dispersed metal with good interaction with surface, reducing metal sintering and deactivation by carbon deposition. In this work, Zr was partially substituted by Ni, Co and Ru on the B site of La2Zr2O7 and Ni was added on the B site of La2Ce2O7 and La2Sn2O7. All the catalysts were prepared by a modified Pechini method. These catalysts were characterized by X-ray diffraction, temperature programmed reduction with H2, fluorescence X-ray, thermogravimetric analysis and scanning electron microscopy coupled to energy dispersive spectroscopic. The catalytic activity was tested in temperatures from 500 to 800°C, at intervals of 50°C. The catalysts containing Ce and Sn in the B site were not active in the dry reforming of methane, neither the catalyst containing Co and Zr in the B site. During stability runs, it was observed that LaZrNi was not stable, presenting rapid deactivation. The containing Ru catalysts were most active that the Ni ones. The results in this study indicate that oxides with pyrochlore structure are promising to catalyze dry (CO2) reforming of methane, they proved to be active even with Ni and Ru content very low at the catalyst surface.
Keywords: Síntese; Catalisadores; Produção de gás; ENGENHARIAS::ENGENHARIA QUIMICA